Erratum to: “Another charadriiform-like bird from the Lower Eocene of Denmark” - Bertelli, Sara Beatriz (2014)
Appendix 1 (Dataset) contains a number of errors and does not fully correspond to the submitted version. The correct Appendix 1 is presented below.